Osteotomy after medial malleolus fracture fixed with magnesium screws ZX00 - A case report - Patrick Holweg; Viktor Labmayr; Uwe Schwarze; Nicole G. Sommer; Martin Ornig; Andreas Leithner (Trauma Case Reports, 2022)
Magnesium alloys have recently become the focus of research, as these implants exhibit suitable biocompatibility and appropriate mechanical properties (Grün et al., 2018 [1]).Through intensive preclinical and clinical investigation, many questions regarding stability, biocompatibility and degradation behavior have been answered (Holweg et al., 2020 [2]). This case report aims to describe handling of these implants in a revision situation, especially when located in situ. To describe available options and relevant considerations, including planning and implementation, a revision surgery of a healed medial malleolus fracture is presented. A medial malleolus fracture was primarily treated by a trauma surgeon with two magnesium screws. Due to an osteochondral lesion of the talus, a revision surgery with osteotomy of the medial malleolus was necessary after 17 months. In this revision, conventional screw removal was not possible due to the degradation of the implant. Taking the degradation and the yield strength of the implant into account, we have chosen on the one hand to over-drill and on the other to leave and perforate the screw.To the best of our knowledge, this is the first case study focusing on the clinical intraoperative site of human bone stabilized with magnesium screws. Despite the hydrogen gas production that occurs during degradation, a solid bone-to-implant interface was evident. With this report, we want to encourage the surgical user to get more involved with resorbable magnesium implants.